COMPUTER-BASED TOEFL (CBT) AS AN INNOVATION IN LEARNING TOEFL - I W.Dana Ardika; I made Rai Jaya Widanta; Ni Luh Chandra Handayani; Ni Wayan Sadiyani; Ni Nyoman Yuliantini (Universitas Negeri Padang, 2017)
The research attempted to design and create software for learning TOEFL. Specifically, it successfully embodied computer-based TOEFL (CBT). The device is a practice test of TOEFL provided for students of Bali State Polytechnic (BSP) particularly and public in general. The execution of research was successfully undertaken pursuant to grant funded by the institution. A set of TOEFL test implemented conventionally as the result of a former developmental result of research was chosen and redesigned to be software-based product. To see whether the test is applicable, a group of ten research participants from Civil Engineering department students were invited to try out the test. Upon their working out the test, they were assigned to fill in questionnaire to obtain necessary input to be used for test revision. Some revision on the test was then done consistent with the input given by research participants. The practice test of TOEFL is considered to be a ready-used practice test for students of BSP and public. However, a number of practice tests shall be developed to provide students who wish to intensively practice working out the test. Moreover, learning center (LC) for TOEFL, whose practice test for TOEFL has been being done conventionally or paper-based type, set in BSP is a compatible place to store and practice TOEFL exercise. It is suggested that there will be the next grant which can fund the further research on making various CBT hardware for TOEFL in BSP